Preparation, sedimentation, and agglomeration of nanofluids - Ilyas, S.U. (Wiley-VCH Verlag, 2014)
Research on nanofluids has increased significantly in the last decade due to the distinctive potential in many applications such as enhanced heat transfer processes, drug delivery systems, and membrane manufacturing processes. The study of dispersion behavior of nanoparticles in liquids is a topic of keen interest towards the preparation of stable nanofluids. A comprehensive review on the recent progress in preparation and stability of nanofluids is presented. Settling of nanoparticles is the only predicament towards preparation of stable nanofluids which takes place due to formation of agglomerates. The settling behavior of nanoparticles in nanofluids and techniques to stop agglomeration are described. Nanofluid preparation techniques, assessment method of stability, and methods to reduce agglomeration are discussed. Importance of nanofluids has increased significantly due to their unique potential for various applications in different fields. The dispersion behavior of nanoparticles in liquids is a key characteristic for preparation of stable nanofluids. Since knowledge of the settling behavior of nanoparticles is crucial for optimizing the degree of stability, recent progress on preparation and stability of nanofluids is reviewed. Â© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.